The result of the application of evaluation criteria in the testing of textbooks (Journal of Educational Sciences, 2023)
Currently, textbook problems in the country are mainly related to the development of high-quality school textbooks. Since the introduction of the updated educational program, this issue has become an actively affected area of competent authorities and scientists, methodologists, teachers, as well as public organizations. This trend, along with the development of textbook studies, contributes to improving the quality of school textbooks. The purpose ofthe proposed article is to determine the results of the testing of textbooks. As part of this goal, it was planned to conduct a pedagogical experiment in schools.When writing the article, methods of analysis, evaluation, synthesis, and comparison were used. Special requirements that should be taken into account when writing a textbook are an unshakable principle in this direction. At the same time, in the process of preparing school textbooks, it is advisable to take into account such important aspects as its clearly directed form, age characteristics of students, learning technologies, socio-social characteristics. The main role of the textbook is that in addition to the systematic training of the student, it contributes to self-education, the formation of his competence to apply the acquired knowledge in practice. While the didactic apparatus of textbooks was analyzed according to several criteria, the implementation of the didactic functions of the textbook was also analyzed on the basis of special criteria. The significance and value of the research article is recognized in the definition of the textbook and the analysis of the results of the approbation examination of textbooks. The results obtained in the course of the study can be used as recommendations when considering the problems of modern textbook studies in the country, as well as in the process of preparing school textbooks, to take as a basis for testing textbooks.Key words: criterion, textbook, content of education, training, approbation, examination, didactics.